Effects of personalised motor imagery on the development of a complex weightlifting movement. Issue 1 (2nd January 2022) - Lindsay, Riki S.; Oldham, Anthony R. H.; Drinkwater, Eric J.; Spittle, Michael; Storey, Adam G.
ABSTRACT: While recent research has indicated that personalised motor imagery (MI) interventions are beneficial to skill performance, little research has investigated the influence of personalised MI on performance of complex weightlifting movements. In addition, this research has rarely compared the efficacy of personalised scripts with instructor-generated scripts and has focused mainly on performance outcomes as opposed to examining the performance processes. A total of 16 individuals novice in the power clean were randomly allocated to one of two conditions: personalised MI, or instructor-generated MI. Participants engaged in a 6-week training intervention, completing three power clean sessions per week. Scripts were listened to five times each week. Results indicated no significant between-condition differences for total forward displacement at 1RM and 90% 1RM (both p = 0.27), but there was a significant difference at 80% of 1RM for total forward displacement between conditions ( p = 0.04, g = −0.94). Differences between conditions for rearward displacement were not significant at any intensities ( p = 0.54). No significant ( p = 0.16–0.97) between-condition differences in kinetic variables were detected at any intensity over the 6-week training period. Findings indicate that the differences in script content do not influence the development of complex weightlifting movements. A large degree of variation was evident when observing the SD's of technical variables for each group which may have contributed to the present results. Future research should seek analysis techniques that allows for further investigation of movement variability and how this impacts the efficacy of personalised MI.